Caminhar para “ri”: humor e imaginário na encruzilhada da formação de professores - Rodrigues, Mário Lúcio Bonotto (2022)
This dissertation is part of the Teaching, Knowledge, and Professional Development research line of the Graduate Program in Education at the Federal University of Santa Maria/RS. The purpose of this research is to understand humor, based on social ideas, explore its characteristics, and find out what happens when it is used in the classroom. How humor interacts in teaching, and learning and how it is involved in teacher education. Methodologically, this research is guide by the qualitative research approach of the self (trans)formation type (HENZ, 2018), in which co-authors are invited to engage in reflective dialogs in which they share their experiences around the proposed topic. At the same time, the research is based on the autobiographical perspective (JOSSO, 2010) and educational research (JOSSO, 2020), in which the author and co-authors engage in a dialog about their teaching trajectories. Six teachers working in differet schools in city of Santa Maria/RS in elementary and high school participed in the data collection. The type of research – self (trans) formation was conducted using the epistemological-political proposal of the investigative – auto (trans) formative dialogical circle (HEINZ, 2015), inspired by Freire's culture circles and educational research (JOSSO, 2020). The Massa Folhada was used to instrumentalize the investigation, using humorous language in its design. This publication was used as a didactic tool following Souto's (2019) and Oliveira's (2013). During its development, in addition to Freire and Josso, the research also relied on theoretical-conceptual contributions from authors such as Catoriadis (1982), Freud (1969), Bergson (1980), Gadamer (1999), Morin (2005), Nóvoa (2009a, 2009b), and others. In the first moment, the production of data for reflection and analysis took place through the narration of the author's life story about the subject of this work – the relationship between humor and the classroom. In the second moment, the production of data took place by conducting six dialogical circles in which the six co-authors' teachers participated. The dialogues address the experience of using humor in the classroom as well as the connection of these experiences to teacher education. The data that emerged from these occasions, the result of the testimonies revealed by the co-authors, were later recorded with the authors called to dialog, resulting in a series of reflections, observations, and clues produced in this research. The studies addressed the influence of the use of the device in the school setting and its connections to affective, cognitive, critical, creative, autonomy, and interpersonal relationsgip among those involved in the teaching-learning process. How humor participates in teacher training, that is, what is the sense and meaning of teaching with humor.